Optimalisasi Kolam Non-Produktif melalui Implementasi Teknologi Autofeeder pada Budidaya Ikan di Desa Karangpring - Ali Rizal Chaidir; Fatoni Riski Ramadani; Virda Ayu Pujiati; Ferdilla Ayza Melani; Bella Inestyas K; Penareal Naibaho; Muhamad Ilham L.H.; Bintang Bima Setyo A; Ahmad Ramadhani; Fahreza Satia Gani; Mochammad Farhan N (IAHN Gde Pudja Mataram, 2026)
The implementation of autofeeder technology in tilapia aquaculture represents a strategic solution to enhance feed efficiency and productivity, particularly for fish farmers in Karangpring Village who manage aquaculture as a side occupation. The primary issue identified in the field is the use of manual feeding methods, which tend to be inconsistent due to the farmers' limited time and busy schedules. This inconsistency negatively impacts fish growth rates and leads to low survival rates, ultimately rendering ponds unproductive. This automated feeding system is specifically designed to regulate feeding schedules, frequency, and dosage consistently and accurately, aligned with the nutritional requirements of the fish at various growth stages. The methodology for this community service activity involves several stages, beginning with field observations, program socialization for users, the installation of autofeeder devices, and technical training on equipment operation. The results demonstrate that the use of autofeeders can effectively reduce feed wastage, which directly contributes to production cost efficiency and the improvement of the Feed Conversion Ratio (FCR) value. Beyond providing operational convenience and reducing the physical daily workload for farmers, this appropriate technology also establishes a more measurable and modern aquaculture management system. Overall, the application of this technology holds significant potential to support the community's economic sustainability by optimizing the revitalization of non-productive pond into more profitable, self-sufficient, and sustainable business units at the rural level.